2019
DOI: 10.18203/issn.2454-5929.ijohns20194948
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of antibiotic resistance in bacteria isolated from tubotympanic type of chronic suppurative otitis media in Chhattisgarh

Abstract: <p class="abstract"><strong>Background:</strong> Chronic suppurative otitis media (CSOM) is a common chronic ear disease and a major health problem in developing countries causing deafness and life threatening complications like meningitis and brain abscess. Early and effective treatment based on the knowledge of causative organism and their antibiotic sensitivity is essential for immediate clinical recovery.</p><p class="abstract"><strong>Methods:</strong> Total of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…As evidenced in this study, CSOM was more common with microbial proliferation in age group of 1–10 years (30.9%) and the age group of 41 years and above. Bacterial pathogens prevalence patterns in CSOM patients within the age group of 1–10 years have been reported in previous studies ( 4 , 24 26 ); with the burden of disease greatest between 6 months and 18 months of age. In contrast to our study, other studies reported maximum number of CSOM cases in the first (1–10 years) and second decades (11–20 years) of life ( 24 , 27 ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…As evidenced in this study, CSOM was more common with microbial proliferation in age group of 1–10 years (30.9%) and the age group of 41 years and above. Bacterial pathogens prevalence patterns in CSOM patients within the age group of 1–10 years have been reported in previous studies ( 4 , 24 26 ); with the burden of disease greatest between 6 months and 18 months of age. In contrast to our study, other studies reported maximum number of CSOM cases in the first (1–10 years) and second decades (11–20 years) of life ( 24 , 27 ).…”
Section: Discussionsupporting
confidence: 71%
“…Bacterial pathogens prevalence patterns in CSOM patients within the age group of 1–10 years have been reported in previous studies ( 4 , 24 26 ); with the burden of disease greatest between 6 months and 18 months of age. In contrast to our study, other studies reported maximum number of CSOM cases in the first (1–10 years) and second decades (11–20 years) of life ( 24 , 27 ). Poor hygiene and unorthodox treatment approaches by care-givers, such as the use of unconventional ear drops and concoctions (oil and honey) into the middle-ear, especially in Nigeria, may initiate the proliferation of opportunistic pathogens, thereby leading to blockage of eustachian tubes in children.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation